Estimation of biomass factor and biomass expansion factor for Populus deltoides, Alnus subcordata and Taxodium distichum in koludeh plantation, Amol - Jamshid Eslamdoust (تحقیقات جنگل و صنوبر ایران, 2014)
Biomass factor is one of the efficient methods for non-destructive estimation of biomass and carbon storage in forest stands. To fulfill the existing lack of biomass data in plantations of Northern Iran, this study derived biomass factor (BF), crown biomass to aboveground biomass ratio (R) and biomass expansion factor (BEF) coefficients for three tree species of Eastern Poplar (Populus deltoides), Caucasian Alder (Alnus subcordata)and Bald cypress (Taxodium distichum) across a 20-years old plantation. For each species, 12 individual trees were felled down. Then the dry weigh of stem, branches, twigs and leaves were separately measured for each tree. The BF values for Eastern Poplar, Caucasian Alderand Bald Cypress were 0.036, 0.007, 0.006 Mg m-3 for branch, 0.055, 0.017, 0.024 Mg m-3 for twigs and 0.041, 0.006, 0.031 Mg m-3 for leaves, respectively. Compared to the other two species, the R value forEastern Poplarwas significantly lower. The BEF values were 0.499, 0.554 and 0.621 Mg m-3 for Eastern Poplar, Caucasian Alder and Bald Cypress, respectively. Although these coefficients are easy to apply and efficient for use, but using them for other plantations must be done with caution, because applying them for other plantations with different stand structure may result in a biased estimation.